2022
DOI: 10.3389/fvets.2021.817183
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Impact of Salsola imbricata Leaf Extract From Taif Against Acrylamide-Induced Hepatic Inflammation and Oxidative Damage: The Role of Antioxidants, Cytokines, and Apoptosis-Associated Genes

Abstract: Salsola imbricata is a herbal plant native to Saudi Arabia, known for its antioxidative and anti-inflammatory properties. This study explored the protective effects of an ethanolic leaf extract of Salsola imbricata against the oxidative stress and hepatic injury caused by acrylamide. Rats received intragastric administrations of 20 mg/kg of body weight of acrylamide to induce hepatic injury, or 300 mg/kg of body weight of Salsola ethanolic extract orally for 7 days before acrylamide administration. The treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Moreover, the ethanolic leaf extracts of this species were found to regulate inflammation, oxidative stress, and antiapoptosis in hepatic inflammations, indicating potential antiinflammatory and antioxidant effects [58] . A similar investigation reported anti-inflammatory and antioxidant effects in inflammatory bowel disease [59] . However, there is a lack of sufficient evidence in the literature to indicate any potential anticancer effect of this plant species.…”
Section: Halocnemum Strobilaceummentioning
confidence: 69%
“…Moreover, the ethanolic leaf extracts of this species were found to regulate inflammation, oxidative stress, and antiapoptosis in hepatic inflammations, indicating potential antiinflammatory and antioxidant effects [58] . A similar investigation reported anti-inflammatory and antioxidant effects in inflammatory bowel disease [59] . However, there is a lack of sufficient evidence in the literature to indicate any potential anticancer effect of this plant species.…”
Section: Halocnemum Strobilaceummentioning
confidence: 69%
“…ZFD rat models have shown higher oxidative stress in myocytes caused by mitochondrial disruption [22]. The overaccumulation of ROS tends to conduct the mitochondria conduct autophagy and then leads to apoptosis releasing this species to the media and promoting in ammation [23,24]. ZDF rats under a HFD are known to develop hypertension with lower mitochondrial biogenesis followed by autophagy [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…A colony of Apolipoprotein E knockout (ApoE KO) rats was established on the Zucker Diabetic Fatty (ZDF) background as previously detailed, utilizing the CRISPR-Cas9 system in combination with superovulation protocols [24,25] (Fig. 1).…”
Section: Animal Model Developmentmentioning
confidence: 99%
“…It has been previously reported that AA caused apoptosis in HL7702 cells (human hepatocyte) by the disturbing cell cycle, disrupting DNA function and activating protooncogene c-jun and c-fos [87]. Studies have shown that AA induces hepatocyte apoptosis, leading to an increase of bax, TGF-β1, and COX-2 and decreases the expression of bcl-2, Nrf2, HO-1, and antioxidant [88]. AA also stimulated apoptosis in HepG2 cell, rat liver cells (e.g., BRL-3A cells and IAR20 cells), and kidney cells, and the miR-27a-5p-Btf3-ATM-p53 axis might play a vital role in the promotion of AA-induced cell apoptosis through disrupting mitochondrial structure and function [89].…”
Section: Acrylamide Induces Apoptosis In Liver Kidney and Lungmentioning
confidence: 99%